Spiritual and Social Changes in a Renewed Society in Uzbekistan - Hurramovich, Togayev Shavkat (European Journal of Life Safety and Stability (2660-9630), 2022)
In this work, the analysis of the complex processes taking place in the modern globalized world cannot be carried out without taking into account socio-philosophical factors. In the new Uzbekistan, life in the spirit of activity and creativity becomes a necessity of life, a social necessity for everyone. The article also provides a philosophical analysis of the principles of social justice in New Uzbekistan, as well as changes in the spiritual and social spheres of society, their features.